Dog Man. Grime and punishment - Pilkey, Dav, 1966-; Garibaldi, Jose (New York, NY : Graphix, an imprint of Scholastic, 2020)
"When Dog Man gets fired by the mayor, he needs his friends' help to combat a new threat"--
Ages 7 and Up
Grades 2-3
GN480L
Decoding demand: 70 (high) Semantic demand: 96 (very high) Syntactic demand: 41 (medium) Structure demand: 83 (very high)
Keywords: Dog Man -- (Fictitious character) -- Juvenile fiction; Dog Man -- (Fictitious character) -- Comic books, strips, etc; Dogs -- Comic books, strips, etc; Police -- Comic books, strips, etc; Crime -- Comic books, strips, etc; Graphic novels; Funny animal comics